Let the amount clayden has be X

Given :

sum of money clayden and jayden have=$784

So x+ amount jayden has =$784

Amount jayden has=$784-x

Clayden spent \( {1 \over 6}\frac{}{}\) =\({1 \over 6}\frac{}{}\)* X

So amount left with clayden=x-\(x = {x \over 6}{}^{}\frac{}{}\)

Amount left with clayden =\( {5x \over 6}\frac{}{}\)

Jayden spends $124

So amount left with jayden = $784-$124-x

So amount left with jayden=$660-x

Given :both have same amount left

Hence - 660-x=\( {5x \over 6}\frac{}{}\)

660*6-6x=5x

660*6=11x

60*6=x

360=x

Amount clayden has =$360